THE IMPACT OF THE COVID-19 PANDEMIC ON TODDLER LANGUAGE AND SPEECH DEVELOPMENT - Nindi Kusuma Dewi; Verlina Maya Gita; Herdhika Ayu Retno Kusumasari; Rizqie Putri Novembriani (Indonesian Journal of Health Care Management, 2022)
One of the most crucial things to observe is the development of children's language and speech. The Covid-19 pandemic, which forces children to stay at home, raises the chance of speech and language deficits in children. The responsibility of parents, schools and health care providers in preventing this is critical. The findings of this study suggest that the Covid-19 pandemic does not affect children's language and speech development as long as parents continue to give a stimulation.